A comparison of physiological parameters between football players and runners competing in various running events - Vucetic, V.; Pucek, M.; Sentija, D. (14th annual Congress of the European College of Sport Science, Oslo/Norway, June 24-27, 2009, Book of Abstracts, 2009)
Introduction: Which type of endurance is crucial in modern football - aerobic or anaerobic? Over the last 20 years football has evolved, especially in terms of athletic preparation of the players, to answer demands of higher intensity of the game and longer field distances covered by players. All those changes require specific training methods and corresponding physiological adaptations of the players. Trained runners, competing in different running events, may serve as role models through the whole range of endurance capacities, from purely anaerobic to ultra-distance aerobic endurance. Therefore, the primary purpose of this study was to compare football players with runners, in parameters of an all-out incremental treadmill test with gas exchange measurements: peak oxygen uptake (VO2max), maximal heart rate (HRmax), maximal running speed achieved in the test (vmax), and speed (vAT) and heart rate (HRAT) at the anaerobic threshold. Methods: Forty-eight national level male runners, competing in running events with predominantly aerobic (AE: 23 middle and long distance runners, 179.6±6.2 cm, 69.1±6.5 kg) or anaerobic (AN: 25 sprinters and 400m runners, 182.5±4.8 cm, 74.5±5.8 kg) metabolic demands, and 45 national/international level football players: 15 defenders (D, 184.4±5.7?cm, 77.2±17.7?kg); 15 midfielders (M, 179.7±7.0 cm, 76.1±6.8 kg) and 15 forwards (F, 180.9±6.0 cm, 77.7±8.3 kg) participated in the study. All subjects performed an incremental treadmill test to exhaustion (speed increase 0.5 km/h every 30 s, 1.5% grade). ANOVA was used to determine differences in observed variables between the groups. Results: As expected, VO2max was significantly higher in AE runners (66.4±4.4 ml/kg/min) than AN runners (58.0±4.1 ml/kg/min, p<0.05), whose values were similar to those in football players (D: 56.4±4.6 ml/kg/min; M: 57.2±5.1 ml/kg/min and F: 57.0±4.5 ml/kg/min). The HRmax differed significantly between AE and AN runners (191±9 : 198±7 bpm, p<0.05), while no difference was present between football players of various playing positions (D : M : F - 192±10 : 193±6 : 193±9 bpm). The AE runners had significantly higher values of vmax and vAT (21.5±1.2 and 16.7±1.5 km/h) than the AN (18.5±1.5 and 13.2±1.2 km/h)(p<0.05). The values of vmax and vAT in football players (D: 18.5±1.1 and 13.6±0.6 km/h; M: 18.8 and 13.8±0.7 km/h; F: 19.3±1.5 and 13.9±0.9 km/h) were similar to the values of AN runners (p>0.05), and hence also significantly lower than in AE runners. Conclusion: The results of this study indicate that, when comparing physiological parameters from an all-out incremental treadmill test between football players and trained runners, the values of football players approximate most closely those of the 400 m runners. This singles out the possible importance of the anaerobic capacity and a high level of sprint endurance in football players.